Study on the compatibility principle of Wutou Decoction based on network pharmacology - Wang Weijie; Yang Xiaonan; Wang Yilin; Pan Hudan; Liu Liang (KeAi Communications Co., Ltd., 2022)
Objective: To investigate the underlying drug enhancement mechanisms of the Chuanwu (Aconiti Radix) and Huangqi (Astragali Radix) combination and toxicity reduction of Chuanwu combined with Gancao (Glycyrrhizae Radix et Rhizoma) in Wutou Decoction (乌头汤, WTD), and to elucidate the compatibility principle. Methods: The active compounds and potential effective targets of the selected combinations were retrieved from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and Traditional Chinese Medicines Integrated Database (TCMID). The toxicity of Chuanwu (Aconiti Radix) was investigated by selecting all five toxic compounds from the literature and the TCMSP database, and obtaining their targets through SwissTargetPrediction. Targets related to rheumatoid arthritis (RA) were searched using DisGeNET, GenCards, and Online Mendelian Inheritance in Man (OMIM). Mutual targets between the drug pairs and RA were selected as potential RA therapy targets. The medicinally active compound-target network was constructed using Cytoscape 3.9.0. Gene ontology (GO) term enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were performed using the Database for Annotation, Visualization, and Integrated Discovery (DAVID) platform. Results: We obtained 191 active compound targets for Gancao (Glycyrrhizae Radix et Rhizoma), 171 for Huangqi (Astragali Radix), and 103 for Chuanwu (Radix Aconiti) (hypoaconitine's target was obtained through literature and SwissTargetPrediction). A total of 5872 genes were obtained for RA. A drug-active compound-target network involving 13 effect-enhancing and nine toxicity reduction targets was constructed. PGR was the main effect enhancement target, and KCNH2 was the main toxicity reduction target. The effect-enhancing targets were related to 23 GO terms (such as positive regulation of transcription from RNA polymerase II promoter, steroid hormone-mediated signaling pathway, plasma membrane, and protein binding) (P < 0.01), and 13 KEGG pathways related to synergism [such as estrogen signaling pathway, cholinergic synapse, and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling pathway]. The toxicity reduction targets were related to 28 GO terms (mainly involves G-protein coupled receptor signaling pathway, plasma membrane, and drug binding) (P < 0.01), and five KEGG pathways related to toxicity reduction (cholinergic synapse, calcium signaling pathway, regulation of actin cytoskeleton, neuroactive ligand-receptor interaction, and serotonergic synapse). Conclusion: The combination of Chuanwu (Aconiti Radix) and Huangqi (Astragali Radix) plays an important effect-enhancing role in WTD and involves the estrogen and PI3K/Akt signaling pathways, with PGR as the core. The Chuanwu (Aconiti Radix) and Gancao (Glycyrrhizae Radix et Rhizoma) combination decreases toxicity in WTD and is associated with the cholinergic synapse and calcium signaling pathways, with KCNH2 as the core.